Natural selection and the 'antiquity of man': Intellectual impacts in the Australian colonies. (December 2021) - Way, Amy
Abstract: Two months before the publication of Charles Darwin's On the Origin of Species (1859), Scottish geologist Charles Lyell announced a consensus on 'the antiquity of man.' Although stemming from separate intellectual traditions, human antiquity and natural selection had such a powerful influence on nineteenth century science that the former is often thought to be an inevitable conceptual and chronological consequence of the latter. Various scholars have argued it was in fact the acceptance of human antiquity that provided a foundation for the intelligibility and eventual acceptance of evolution by natural selection. This article investigates how these two interwoven theories affected understandings of human antiquity in Australia; itself an under-examined topic in Australian scholarship. Indeed, most historians maintain Australia's human antiquity was not 'discovered' or broadly understood until the advent of radiocarbon dating and professional archaeology in the 1960s. This over-simplified narrative has only recently begun to be reassessed. To contribute to this reassessment, and to the broader reclamation of human antiquity as a historical subject, this article focuses on the early decades of human antiquity's dissemination in Australia, examines its complex relationship with natural selection, and ultimately challenges narratives of its 'recent' discovery.